2016
DOI: 10.1016/j.ijscr.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder’s clear cell renal carcinoma metastasis: A case report

Abstract: HighlightsContribute to the comprehension of rare mestatic disease in clear cell renal carcinoma.Underline that non only primary tumors develop in the gallbladder.Increasing suspect of metastatic disease in patients with renal cell carcinoma will improve medical care of this patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Thus, it cannot be stated unconditionally that a single metastasis in the gallbladder is common or not. Castro Ruiz et al also reported that cholecystectomy with R0 resection was shown to be the only factor that increases survival 4 . Surgical treatment should be considered a positive form of treatment when the metastatic lesion is solitary and resectable.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it cannot be stated unconditionally that a single metastasis in the gallbladder is common or not. Castro Ruiz et al also reported that cholecystectomy with R0 resection was shown to be the only factor that increases survival 4 . Surgical treatment should be considered a positive form of treatment when the metastatic lesion is solitary and resectable.…”
Section: Discussionmentioning
confidence: 98%
“…The surface is covered by gallbladder epithelium. Other lesions like adenomyomatosis or chronic cholecystitis may be associated [12]. Immunohistochemical staining is performed to assess the diagnosis and shows positivity to AE1/AE3, Vimentin, CD10 and RCC with no expression of S100, cytokeratin or CEA.…”
Section: Discussionmentioning
confidence: 99%
“…Usual metastasis sites are lung, bone, and liver 3,5 . The gallbladder is an unusual site for renal cell carcinoma metastasis; only a few cases have been reported, and most of them (48%) are located at fundus as our patient 1–9 . To our knowledge, only 1 case has been reported with 18 F-FDG PET/CT findings 6 .…”
mentioning
confidence: 69%
“…3,5 The gallbladder is an unusual site for renal cell carcinoma metastasis; only a few cases have been reported, and most of them (48%) are located at fundus as our patient. [1][2][3][4][5][6][7][8][9] To our knowledge, only 1 case has been reported with 18 F-FDG PET/CT findings. 6 Throughout the available follow-up of solitary gallbladder metastatic patients for 1.1 years, none of them had the remaining disease.…”
mentioning
confidence: 95%